Onomatopoeic Words in Slovak: Everyday Use and Stylistic Function - Gregová, Renáta (Slavistica Vilnensis, 2022)
Onomatopoeias — words that echo sounds from the extra-linguistic reality — are usually understood as units representing direct relationship between form and meaning. Lexical onomatopoeias are part of a language system and their meaning can be found in dictionaries. It is assumed that onomatopoeias are crucial in communication by and to infants and are also considered important stylistic devices in poetry. However, they seem to be only marginal in adults’ speech. This paper presents the results of an analysis of the understanding of Slovak onomatopoeias in everyday communication as well as of the stylistic dimension of these expressions in poetry. First, attention was paid to the comprehension of sound-imitating words in context by the sample of 30 native Slovak language speakers. Then, a sample of ten Slovak poems, well-known due to their usage of various sound-symbolic elements (onomatopoeias included) as stylistic devices, was examined to verify the supposed stylistic dimension of onomatopoeias in poetry. The results indicate that the understanding of the real meaning of lexical onomatopoeias depends on the specifics of the context and that onomatopoeias play a less important role in poetry than expected.